MAJORIZATION TYPE INEQUALITIES VIA GREEN FUNCTION AND HERMITE'S POLYNOMIAL - Khan, M. Adil; Latif, N.; Pecaric, J. (Journal of the Indonesian Mathematical Society, 2016)
The Hermite polynomial and Green function are used to constructthe identities related to majorization type inequalities for convex function. By usingÂ  Cebysev functional the bounds for the new identities are found to develop the Gruss and Ostrowski type inequalities. Further more exponential convexity together with Cauchy means is presented for linear functionals associated with the obtained inequalities.DOI : http://dx.doi.org/10.22342/jims.22.1.251.1-25